Foundations of Islamic governance a Southeast Asian perspective - Maszlee Malik 1974- (Routledge studies on Islam and Muslims in Southeast Asia, 2017)
The aim of this book is to explore and analyze the Islamic axioms, foundation principles and values underpinning the field of governance in an attempt to construct the architectonics of a new systemic and dynamic theory and formulate the articulation of 'Islamic governance'.